Positive Urine Cultures: A Major Cause of Inappropriate Antimicrobial Use in Hospitals?. Issue 4 (2009) - Silver, Samuel A; Baillie, Laura; Simor, Andrew E
Abstract : INTRODUCTION: Urine specimens are among the most common samples submitted for culture to microbiology laboratories. The objectives of the present study were to describe the indications for obtaining urine cultures in a cohort of hospitalized patients, and to determine the appropriateness of antimicrobial therapy in response to urine culture results. METHODS: The study was performed at a teaching hospital with an adjoining long-term care facility from June 1 to July 31, 2006. The medical records of nonpregnant adult patients with and without bacteriuria were reviewed. A symptomatic urinary tract infection was defined as the presence of bacteriuria in a patient with fever or urinary symptoms; asymptomatic bacteriuria was defined as bacteriuria without urinary symptoms and no infection evident at another site. RESULTS: Medical records of 335 eligible patients (64% male; mean age 68 years) were reviewed, including all 137 with bacteriuria, and 198 with negative urine cultures. In total, 51% of the urine specimens were obtained from an indwelling urinary catheter, and 28% were voided urine samples. Confusion (57%) and fever (36%) were the most common indications noted for obtaining the urine cultures. Only 34 patients (25% of those with positive urine cultures) met the criteria for a symptomatic urinary tract infection; 67 (49%) had asymptomatic bacteriuria and 36 (26%) had infection at a nonurinary site. Of those with asymptomatic bacteriuria, 64% received antimicrobial therapy for a total of 347 days. Confused patients with asymptomatic bacteriuria were more likely to be treated than were bacteriuric patients without altered mental status (OR 1.8, 95% CI 1.2 to 4.1; P=0.03). CONCLUSIONS: Urine cultures are frequently obtained from hospitalizedpatients, evenintheabsenceofurinarysymptoms.Asymptomatic bacteriuria is often treated in these patients, and accounts for a substantial burden of inappropriate antimicrobial use in hospitals. Effective strategies to improve urine culture ordering and antimicrobial utilization in hospitals need to be implemented.